The Shaping of Confucius’s Image in Early Western Writings: António de Gouvea’s Life of Confucius (1654) and Inter-Order Interactions - ZHANG, Baobao (Journal of Research for Christianity in China (JRCC), 2026)
This article examines the sustained and complex process through which Western missionaries in China constructed the image of Confucius during the seventeenth and eighteenth centuries. Previous scholarship has generally taken the “Life of Confucius” included in Sapientia Sinica (1662) by Prospero Intorcetta and Ignatio da costa as the starting point of this tradition. By uncovering an earlier “Life of Confucius” contained in António de Gouvea’s Historia de China dividida em seis idades (1654), this study reveals a previously overlooked origin of this line of writing. Focusing on Gouvea’s account, the article analyzes how early Jesuits fashioned Confucius as an intellectual and moral authority intelligible to European audiences. It further situates this construction within a broader context of inter-order exchange and controversy. Through a comparison of Jesuit and Dominican interpretations—particularly concerning the “kongzi guan qi qi孔子观欹器,” the dictum “Jun zi bu qi君子不器,” and Confucius’s religious status—the article demonstrates how divergent readings of Confucius became entangled with the broader dynamics of the Chinese Rites Controversy. It argues that the early Western image of Confucius was not a unilateral Jesuit construction, but rather the product of sustained interaction, negotiation, and polemical engagement among different missionary orders.